Jurisprudential Rulings Related To Digital Currencies And Linguistic Connotations/ الأحكام الفقهية المتعلقة بالعملات الرقمية ودلالاتها اللغوية - Medbesh, Ahmad Bin Jaber; Khalil, Ghadeer Ahmed Sheikh (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
It aims to describe of the provisions of Islamic Sharia of encrypted digital currencies and its linguistic implications. Using a scientific jurisprudential methodology. It also discusses the search for the credibility of encrypted digital currencies that comply with the provisions of Islamic Sharia. The results that production is a basis in addition to the value that financing contributes and its linguistic implications, with the most prominent costs as high. Efficiency of Islamic financial financial services, and that the engineering of financial products is based on innovations and creating new solutions for financial management or reproducing the trader in traditional financial finance, with the participation of a strong entitlement basis and participation in many of the basis of effective management of Islamic finance systems, and a statement of the trading rule in those currencies, This is to achieve economic fundamentals and legal credibility and its linguistic implications.